Cerebral small vessel disease with hemorrhagic stroke related to COL4A1 mutation: A case report. Issue 1 (5th December 2019) - Nandeesh, Bevinahalli N.; Bindu, Parayil Sankaran; Narayanappa, Gayathri; Chickabasaviah Yasha, T.; Mahadevan, Anita; Kulanthaivelu, Karthik; Santosh, Vani
Abstract : Stroke is a major cause of mortality and morbidity with a wide variety of etiological risk factors. Cerebral small vessel disease (SVD) is an important cause of stroke in the young with several hereditary disorders affecting these small blood vessels. Mutations in the COL4A1 gene ( COL4A1 ) have been shown to be associated with a broad range of disorders including hemorrhagic stroke, myopathy, glaucoma and others. We report a rare case of stroke in an intellectually disabled 18‐year‐old girl with radiological evidence of basal ganglia microbleeds, periventricular white matter signal changes and porencephalic cyst. Ophthalmic examination revealed bilateral microcornea and Axenfeld–Rieger anomaly. At autopsy there were hemorrhagic lesions at multiple sites within the brain. Histology revealed thickened small‐caliber vessels which demonstrated disruption and fragmentation of the basement membrane by collagen type IV alpha 1 immunohistochemistry and by electron microscopy. A missense COL4A1 mutation involving glycine residue was detected in the patient. The present case illustrates the clinicopathological spectrum of COL4A1 ‐related cerebral SVD presenting as hemorrhagic stroke in the young with porencephaly, intellectual disability, and Axenfield–Rieger anomaly and thus adds to the clinical heterogeneity of this genetic disorder.